Compared the Efficiency of Two Methods (Chemical and Biological) for Removal (Cadmium, Copper and Zinc) from Contaminated Water - Muntaha N. Althweni; Jenan H. Mohammed; Mayami H. Awad; Teba S. Ganee (Engineering and Technology Journal, 2016)
In the present study two methods were used to compare the efficiency of removing heavy metals (cadmium, copper and zinc) from contaminated water, and by applying the method of adding a chemical polymer dynamically (Alginic acid) and the method of adding a biological pure culture type of (green algae), different concentrations, respectively (1.0, 0.75, 0.5, 0.25 ppm) was prepared for each element. Both of these methods have been applied and the same working conditions of temperature and pH of the time (72 hours), and then detect the level of residual concentrations of the elements mentioned using Flame atomic spectroscopy technique for measuring the absorbance. The results showed that the two methods effective in drag tested with the superiority of biopolymer algae free in reducing cadmium and copper. While convergence efficient ways to remove the zinc from aqueous media contaminated.